The broad-spectrum anti-emetic activity of the novel non-peptide tachykinin NK1 receptor antagonist GR203040. - Gardner, C; Twissell, D; Dale, T; Gale, J; Jordan, C; Kilpatrick, G; Bountra, C; Ward, P (1995)
1. Following our earlier observations that the tachykinin NK1 receptor antagonist CP-99,994 is an effective anti-emetic in ferrets, we have examined the anti-emetic effects of a more potent and novel NK1 receptor antagonist, GR203040, against various emetic stimuli in the ferret, dog and house musk shrew (Suncus murinus). 2. In ferrets, GR203040 (0.1 mg kg-1 s.c. or i.v.) is effective against emesis induced by radiation, cisplatin, cyclophosphamide, copper sulphate, ipecacuanha or morphine. 3. In animals in which emesis had been established with cisplatin, GR203040 (1 mg kg-1 s.c.) was fully effective as an interventional treatment. No further emesis was seen in animals treated with GR203040 whilst saline-treated animals continued to vomit. 4. GR203040 (0.1 mg kg-1 s.c.) retains anti-emetic efficacy in the ferret, even when given as a 6 h pretreatment, indicating that this compound has a long duration of action. The compound is also effective orally at the same dose, when given as a 90 min pretreatment. 5. GR203040 (0.1 mg kg-1 i.v.) is fully effective against ipecacuanha-induced emesis in the dog. 6. GR203040 is effective against motion- and cisplatin-induced emesis in Suncus murinus. These effects were seen at doses an order of magnitude greater than those shown to be effective against cisplatin in the ferret. 7. In conclusion, GR203040 is a novel anti-emetic agent, and the broad spectrum of anti-emetic activity, together with activity observed in three species, suggests that this compound is worthy of clinical investigation.